Does Vrancea Nappe go West? (Geo-Eco-Marina, 2023)
The presence of the Vrancea Nappe beneath the Dacian Basin synkinematic and post-tectonic cover from the SE Carpathians has been challenged for a while back. Available subsurface data shows its presence can be interpreted in the Bend Zone and eastern Getian Basin. It is proposed that the Vrancea Nappe is present in the Bend Zone, in a halfwindow west of the Teleajen Valley and up to Dâmboviţa Fault(DF), which is here preliminarily called Dâmboviţa Halfwindow. The Vrancea Nappe frontal line is tentatively outlined on some 60 km length to the Getian Basin also based on the outwards disappearing of the pre-Burdigalian deposits in the Pericarpathian Nappe. In addition, the subsurface information down to the drilled Oligocene sequences shows the facies individuality of this nappe as compared with the inwards Tarcău Nappe one.
Keywords: Eastern Carpathians; Getian Basin; Vrancea Nappe; Bend Zone; Vrancea Line; Petroleum System